The Evaluation of Digital Lending: Innovation, Challenges, and Future Prospects. A Systematic Review - Sekhar, Kunchakara Raja; Saheb, Shaiku Shahida; Chakka, Naga Bhavani; Charugulla, Sirisha (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026, 2026)
Digital lending, driven via fintech innovations like peer-to-peer (P2P) platforms, is revolutionized with the Zopa app; financial accessibility has significantly improved, connecting borrowers and lenders through the internet, offering an efficient, transparent, and inclusive alternative to traditional banking. The research aims to evolve the landscape of digital lending in India and the compliance challenges faced by digital lending platforms in adhering to RBI along with other financial regulations. Study leveraging a systematic literature review (SLR) using the PRISMA model coupled with Scopus and Science direct data 2019-2025). Considered full-text assessment, chosen relevant documents for the synthesis matrix analysis. Comprehensive examination highlights, that digital lending improves access to credit, although these platforms in India and globally reveal disparities such as regulatory gaps, cybersecurity threats, information asymmetry, and unethical lending practices. This study suggests the role of emerging technologies, including artificial intelligence (AI) and blockchain, in mitigating risks, enhancing credit scoring models, plus improving regulatory compliance. The findings advocate for a holistic approach that fosters financial innovation while addressing systematic risks. Future research should explore the long-term stability of P2P lending platforms, alternative credit-scoring techniques, and the socio-economic impact of digital lending, particularly in emerging economies.